An assessment of training and employee performance: evidence from the health sector in Ashanti Region - Boaitey, Evelyn (2015)
A thesis submitted to the Department of Managerial Sciences, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Business Administration (HRM option).